Minimally Invasive Reconstruction of the Lateral Ankle Ligaments Using Semitendinosus Autograft or Tendon Allograft. (October 2014) - Xu, Xiangyang; Hu, Mu; Liu, Jinhao; Zhu, Yuan; Wang, Bibo
Background: The purpose of the study was to retrospectively compare the therapeutic effect between semitendinosus autograft and tendon allograft for lateral ankle ligaments reconstruction. Methods: From September 2006 to June 2011, 68 patients (41 males, 27 females) with chronic ankle instability underwent anatomical reconstruction of the lateral ligaments using semitendinosus autograft (autograft group, 32 patients) or tendon allograft (allograft group, 36 patients) via a minimally invasive approach. All patients were followed up for at least 12 months. The American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Scale score (AOFAS score) and stress tests were used to evaluate the clinical outcomes. Operation time, time to heal and complications were also recorded. Results: Compared with allograft group, the average operation time was significantly increased (85.5 ± 11.5 minutes vs 58.1 ± 10.2 minutes, P < .0001), but the mean time to heal was significantly shorter (11.2 ± 4.1 months vs 13.5 ± 5.2 months, P = .0458) in the autograft group. Although the mean AOFAS score was significantly increased at the final follow-up in the autograft group (95.1 ± 7.5 vs 62.3 ± 8.2, P = .0001) and allograft group (94.8 ± 5.5 vs 60.2 ± 8.4, P < .0001), no significant difference in AOFAS was found between these 2 groups. Similarly, there was no significant difference in talar tilt or shift between autograft and allograft groups. In addition, no patients complained of weakness or disability at the donor site in the autograft group, while incisional swelling was observed in 4 patients in the allograft group, which was resolved via dressing change, oral use of indomethacin or dexamethasone. Conclusion: Reconstruction of the lateral ankle ligaments using a semitendinosus tendon autograft and a minimally invasive approach was safe and effective for ankle instability with a relatively short time for healing and minimal donor site problems. Level of Evidence: Level III, comparative case series.